2015
DOI: 10.3389/fnbeh.2015.00150
|View full text |Cite
|
Sign up to set email alerts
|

Threat affects risk preferences in movement decision making

Abstract: Emotional states such as sadness, anger, and threat have been shown to play a critical role in decision-making processes. Here we addressed the question of whether risk preferences are influenced by postural threat and whether this influence generalizes across motor tasks. We examined risk attitudes in the context of arm-reaching (ARM) and whole-body (WB) leaning movements, expecting that increased postural threat would lead to proportionally similar changes in risk-sensitivity for each motor task. Healthy you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This idea is further supported by findings indicating that aging impacts the integrity of the cerebellum (Luft et al, 1999 ; Raz et al, 2005 ), which regulates the sensitivity to errors driving motor adaptation (Criscimagna-Hemminger et al, 2010 ). Alternatively, older adults are in general risk averse (Albert and Duffy, 2012 ; Tymula et al, 2013 ) and risk-sensitivity has been shown to influence sensorimotor control (Nagengast et al, 2010 ; O'Brien and Ahmed, 2015 ) and motor adaptation (Trent and Ahmed, 2013 ). Thus, it is possible that the aged motor system exploits prior experiences rather than exploring new movements to avoid risks such as falling, which have more serious consequences in old than young populations (Talbot et al, 2005 ; Mitchell et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This idea is further supported by findings indicating that aging impacts the integrity of the cerebellum (Luft et al, 1999 ; Raz et al, 2005 ), which regulates the sensitivity to errors driving motor adaptation (Criscimagna-Hemminger et al, 2010 ). Alternatively, older adults are in general risk averse (Albert and Duffy, 2012 ; Tymula et al, 2013 ) and risk-sensitivity has been shown to influence sensorimotor control (Nagengast et al, 2010 ; O'Brien and Ahmed, 2015 ) and motor adaptation (Trent and Ahmed, 2013 ). Thus, it is possible that the aged motor system exploits prior experiences rather than exploring new movements to avoid risks such as falling, which have more serious consequences in old than young populations (Talbot et al, 2005 ; Mitchell et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is strong evidence that the subjective valuation of movement-related costs such as time and probability differ from their objective values [2,35]. When considering the subjective value of these costs, models of movement control can better predict movement-related behaviours [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Consistency in risk-taking behaviour, which could be considered a concept analogue to misjudgment, was studied by O’Brien and Ahmed [ 14 , 15 ]. Subjects that overestimate their ability might be inclined to accept higher risk than under-estimators [ 12 ], who in turn, are more likely to bypass activities to avoid risk exposure out of fear of falling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%